Role of dyslipidemia in preeclamptic overweight pregnant women - Seyede Hajar Sharami; Azita Tangestani; Roya Faraji; Ziba Zahiri; Azam Amiri (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Obesity is an independent risk factor of preeclampsia with unknown mechanism and hyperlipidemia might be a probable case of it. Objective: The objective of this study was to determine the role of hyper-triglyceridemi in association with high prepregnancy body mass index and the risk of preeclampsia. Materials and Methods: The authors conducted this case-control study of 42 preeclamptic and 41 normotensive overweight pregnant women. The two groups were comparable with respect to age, gestational age, and body mass index. Blood samples were collected at the time of diagnosis of preeclampsia, after 14 hour fasting to determine plasma lipid concentrations. Enzymatic photometric tests were used to determine lipid profile. Data was analyzed with independent "t-test", Chi-square and one-way ANOVA and post HOC Tukey HSD test. The statistical significance was set at 0.05 levels. Results: In the subjects with preeclampsia, serum triglyceride and total cholesterol levels were significantly increased and plasma HDL-cholesterol concentrations were decreased compared with the controls, (p<0.05), but plasma LDL cholesterol levels didn't differ between the two groups. Women who developed severe preeclampsia had higher concentrations of TG and cholesterol and lower levels of HDL compared to noromotensive group. Mean TG: 375.16 vs. 202.85, p<0.001, Mean cholesterol: 245.64 vs. 214.32, p=0.04, Mean HDL: 40.80 vs. 48.95, p=0.03). Conclusion: We noted that dyslipidemia, particularly hypertriglyceridemia was highly correlated with prepregnancy high BMI in preeclamptic women. These findings continue to support a role for dyslipidemia in BMI related preeclampsia